Brain Based Learning Berbantuan Media Gambar dalam Pembentukan Karakter Siswa Perspektif Pendidikan Agama Islam - Desvyana Wahyu Eka Safitri; Ria Yulia Gloria; Lala Bumela (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Character education has become an important concern in elementary education due to the increasing need to develop students’ moral, social, and religious values alongside academic achievement. This study aimed to analyze the implementation of Brain Based Learning (BBL) assisted by picture media in character building, examine its effect on students’ character formation, and explore its relevance to Islamic Religious Education values. The study employed a quantitative approach using a quasi-experimental design involving 50 fifth-grade students of SD Karakter 2 Gunung Puteri, Bogor Regency, consisting of an experimental class and a control class. Data were collected through observation, questionnaires, and tests, then analyzed using descriptive statistics, t-test, F-test, and coefficient of determination. The findings indicate that the implementation of Brain Based Learning assisted by picture media positively contributed to students’ character development by creating active, meaningful, and enjoyable learning experiences. Various character aspects, including responsibility, honesty, respect, tolerance, perseverance, and love of God, showed positive development during the learning process. Statistical analysis revealed that Brain Based Learning and picture media had a positive and significant effect on character formation, both partially and simultaneously. Furthermore, the developed character values were closely related to the objectives of Islamic Religious Education, particularly in fostering faith, morality, responsibility, cooperation, tolerance, and noble character. These findings suggest that Brain Based Learning assisted by picture media can serve as an effective instructional strategy for strengthening character education while supporting the internalization of Islamic values in elementary school students.